Prywatyzacja jako narzędzie polityki strukturalnej w Polsce w latach 1990-2006 - Wojarska, Magdalena; Czeszejko-Sochacka, Małgorzata (Privatisation as an Instrument of Structural Policy in Poland between 1990 and 2006, 2008)
The main aim of the article was determination of privatisation place in structural policy as well as identification the directions of transformation which were realized in regions. The analisis showed that privatisation policy is an element old structural policy of the state. Moreover collected statistic data led to the conclusion that sector of state enterprise has been cut down in Poland between 1990 and 2006 about 89,2%. The most popular transformation method has been direct privatisation, used in 39,5% cases. In the article all regions in Poland were divided into three groups for the purpose of using this special procedure. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 168-177